2022
DOI: 10.1111/scs.13064
|View full text |Cite
|
Sign up to set email alerts
|

Associations between nurse managers’ leadership styles, team culture and competence planning in Norwegian municipal in‐patient acute care services: A cross‐sectional study

Abstract: Background Increased complexity in the primary healthcare services has followed in the wake of health reforms and reveals the need for competence enhancement in the nursing services. Effective and visionary leadership, sufficiently qualified staff and cooperation among professionals are considered as key measures to safeguard quality in the services. Aims To identify which leadership styles characterise first‐line nurse managers in Norwegian municipal in‐patient acute care (MipAC) units and to investigate how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
2
0
4
Order By: Relevance
“…Enfermeiros apontaram que seus líderes em instituições de APS procuram criar ambientes de trabalho onde a equipe de enfermagem possa ter autonomia ao exercer suas funções através de distribuição igualitária de recursos e interações positivas com outros profissionais de saúde (POGHOSYAN; BERNHARDT, 2018). A cultura de equipe e o planejamento de competências também foram associados à liderança transformacional por enfermeiros que exercem suas funções em instituições de saúde primária (VATNØY et al, 2022). Enfermeiros que atuam na APS enfatizaram ainda que adquirir características pertinentes ao líder transformacional é difícil, pois, demanda tempo e experiência, uma vez que ao se formaram eles não se sentem totalmente aptos para exercerem a liderança (BRZOZOWSKI et al, 2022;.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Enfermeiros apontaram que seus líderes em instituições de APS procuram criar ambientes de trabalho onde a equipe de enfermagem possa ter autonomia ao exercer suas funções através de distribuição igualitária de recursos e interações positivas com outros profissionais de saúde (POGHOSYAN; BERNHARDT, 2018). A cultura de equipe e o planejamento de competências também foram associados à liderança transformacional por enfermeiros que exercem suas funções em instituições de saúde primária (VATNØY et al, 2022). Enfermeiros que atuam na APS enfatizaram ainda que adquirir características pertinentes ao líder transformacional é difícil, pois, demanda tempo e experiência, uma vez que ao se formaram eles não se sentem totalmente aptos para exercerem a liderança (BRZOZOWSKI et al, 2022;.…”
Section: Resultsunclassified
“…Estudos incluídos nesta revisão enfatizaram que o estilo de liderança do gerente de enfermagem influencia a qualidade do cuidado (BRZOZOWSKI et al, 2022;LARA JAQUE et al, 2020;POGHOSYAN;BERNHARDT, 2018;VATNØY et al, 2022). Além disso, observou-se a importância de que gerentes de enfermagem adotem a liderança transformacional na APS (BRZOZOWSKI et al, 2022;POGHOSYAN;BERNHARDT, 2018;VATNØY et al, 2022). Portanto, instituições de ensino devem atentar para capacitar estudantes para serem líderes que inspirem e motivem suas equipes no futuro (BRZOZOWSKI et al, 2022;LARA JAQUE et al, 2020;.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Sistem dari layanan kesehatan selalu berada dalam kondisi bersaing untuk meningkatkan kesehatan masyarakat dan di saat yang bersamaan menghindari peningkatan biaya kesehatan (Specchia et al, 2021). Penelitian sebelumnya telah menunjukkan bahwa peran pemimpin dan gaya kepemimpinan yang diterapkan dapat mempengaruhi kinerja karyawan serta kinerja dari sistem layanan kesehatan itu sendiri (Daswati et al, 2021;Vatnøy et al, 2022)). Maka dari itu, teori kepemimpinan perlu terus dilakukan penelitian, baik untuk mengeksplorasi perannya terhadap aspek pelayanan kesehatan ataupun untuk menilai relevansinya dengan masa depan yang selalu berubah.…”
Section: Hasil Penelitian Pengaruh Gaya Kepemimpinan Dalam Penelitian...unclassified
“…Using extant supporting research, we provide rationale for its strength as an intervention and call attention to it as a great tool in nurturing teams in their lifespan. 1) review [and more recently, Vatnøy et al (28)] corroborated the importance of team leadership-which, as many have found (29), can help members coordinate their collective resources in accomplishing the team's work (27,30). Furthermore, as the team coaching literature has evolved, it has been mostly conceptualized as a leadership strategy that both internal and external coaches can provide (31).…”
Section: Introductionmentioning
confidence: 99%